What Determines The World Heritage List? An Econometric Analysis - Bruno S. Frey; Paolo Pamini; Lasse Steiner (Center for Research in Economics, Management and the Arts (CREMA), 2011)
The official intention of the UNESCO World Heritage List is to protect the global heritage. However, the existing List is highly imbalanced according to countries and continents. Historical reasons, such as historical GDP, population, and number of years of high civilization, have a significant impact on being included on the List. In addition, economic and political factors unrelated to the value of heritage, such as rent seeking by bureaucrats and politicians, the size of the tourist sector, the importance of media, the degree of federalism, and membership in the UN Security Council, influence the composition of the List.
Keywords: Z11; F5; H87; 330; global public goods; world heritage; international organizations; international political economy; culture